Optomechanical Design of a Space Telescope Primary Mirror - Rehman, Saeed Ur (Department of Electrical Engineering, 2023)
The primary mirror is the most critical component of a space-borne telescope. The size of the primary mirror is the main driver for the resolution of the telescope. A high resolution telescope requires a larger primary mirror with the high-precision requirement of deformation due to space thermal loads, gravity loads in AIT environment and pressure loads during surface polishing. In addition to this, mass is also an important criterion. Telescope mass is also derived from the mass of the primary mirror. So, a lightweight primary mirror with sufficient stiffness to avoid distortion due to gravity and thermal loads is necessary to get the required optical performance from high-resolution telescopes. It will also keep the mirror within its allowable stress limit with a sufficient Margin of Safety in external acceleration and vibrational launch loads so that it can survive during launch. Flexure support is also a very critical component of the primary mirror assembly. The aim of flexure support is to isolate the mirror surface so that it will not distort because of thermal expansion/contraction, gravity loads and mounting stresses. Stiffness of the flexure is a very critical design variable. It should be enough stiff that there will be no plastic deformation due to launch loads and it must be flexible enough that it can isolate the optical surface from the distortion of the optical bench. Researchers have worked on the design solution for large size lightweight primary mirrors and based on the research they have proposed their optimized design for primary mirror and its support. The objective of this research is to propose the optomechanical design solution the primary mirror of a space telescope. It includes designing of the lightweight structure of the primary mirror based on Finite Element Analysis. Open back pocketing will be used to lightweight the primary mirror. The primary mirror support will be designed to a-thermalize and isolate the primary mirror from the external structure. The performance of the primary mirror will be analyzed for deflection due to gravity & thermal loads and stress due to external acceleration and thermal loads based on Finite Element Analysis. Trade off study will be performed for the selection of mirror material and the pocketing shape. The impact of different design variables for pocketing material will be analyzed. On the basis of these analyses a comprehensive workable design solution will be proposed for the Primary Mirror that meet the requirements for surface error and have enough strength to bear launch loads.